Analysis of Calcium Levels in Yoghurt Drinks Using a UV-Visible Spectrophotometry Method - Elfina Salsabila; Erfan Priyambodo (Universitas Negeri Semarang, 2023)
This experiment study aims to determine the levels of calcium in yoghurt drink using the UV-Vis spectrophotometric method. UV-Vis spectrophotometry was used to measure calcium concentrations in murexids by observing the color change that occurred as a result of the synthesis of calcium complex compounds under alkaline circumstances. Both qualitative and quantitative procedures were used in the study. The presence of calcium in yogurt was evaluated using a qualitative method. The murexid solution, the standard calcium solution (CaCl2.2H2O), the maximum wavelength, the standard curve, and the calcium content of yogurt were all measured in a quantitative analysis. The findings confirmed that calcium levels in yogurt drinks may be measured using UV-Visible spectrophotometry. Maximum wavelength generated in this study was 523 nm, and the research used calcium concentrations of 0.2 ppm, 0.4 ppm, 0.6 ppm, 0.8 ppm, and 1.0 ppm. Absorbance measurements taken from calcium standard solutions at these concentrations ranged from 0.264 to 0.288 to 0.304 to 0.351 to 0.424. Linear regression was performed, and the derived equation is y = 0.1915x + 0.2113 with R = 0.9575 and R2 = 0.9168. Sample A had an average calcium concentration of 2.0397 mg/mL, as shown by the absorbance values of 0.521 and 0.555. In contrast, sample B's calcium concentration was 2.2895 mg/mL. Sample B of the yogurts had a calcium concentration of 2.2895 mg/mL, making it the superior option. Keywords: Calcium, Murexide, UV-Vis Spectrophotometry, Yogurt